Phytophthora pathogens threaten rare habitats and conservation plantings - Susan J. Frankel; Janice Alexander; Diana Benner; Janell Hillman; Alisa Shor (Sibbaldia, 2020)
Phytophthora pathogens are damaging native wildland vegetation including plants in restoration areas and botanic gardens. The infestations threaten some plants already designated as endangered and degrade high-value habitats. Pathogens are being introduced primarily via container plant nursery stock and, once established, they can spread to adjacent areas where plant species not previously exposed to pathogens may become infected. We review epidemics in California – caused by the sudden oak death pathogen Phytophthora ramorum Werres, De Cock & Man in ‘t Veld and the first USA detections of P. tentaculata Kröber & Marwitz, which occurred in native plant nurseries and restoration areas – as examples to illustrate these threats to conservation plantings.